2014
DOI: 10.1185/03007995.2014.936188
|View full text |Cite
|
Sign up to set email alerts
|

Prediction model for penile prosthesis implantation for erectile dysfunction management

Abstract: The presence and extent of specific medical history factors at the time of erectile dysfunction diagnosis predict an individual's future likelihood of penile prosthesis. Calculating the likelihood of penile prosthesis implantation based on the weight of these factors may assist clinicians with the definition of a care plan and patient counseling. The precision of the model may be limited by factors beyond medical history information that possibly influence the decision to proceed to surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…DED is among the 2 main reasons for implantation of an implant. Segal et al (2014) developed a prediction tool based on a patient's clinical history to determine likelihood of ultimately receiving a penile prosthesis (Segal, 2014). Inclusion criteria were18 years of age with 1 year of continuous enrollment at the first diagnosis of ED.…”
Section: Penile Implantsmentioning
confidence: 99%
“…DED is among the 2 main reasons for implantation of an implant. Segal et al (2014) developed a prediction tool based on a patient's clinical history to determine likelihood of ultimately receiving a penile prosthesis (Segal, 2014). Inclusion criteria were18 years of age with 1 year of continuous enrollment at the first diagnosis of ED.…”
Section: Penile Implantsmentioning
confidence: 99%
“…A study by Tal et al found that men who had surgery as an initial treatment (versus radiotherapy), were of a younger age, were of African/American/Hispanic race, were unmarried, and were living in a geographic region other than the North-east were more likely to utilize penile implants 25 . Similarly, in a retrospective analysis of claims data from Medicare & Commercial databases of 3928 men undergoing penile prosthesis, Segal and Burnett elucidated the factors with the greatest predictive strength of penile prosthesis implantation, which included a diagnosis of prostate cancer, a diagnosis of diabetes mellitus and previous treatment with first-line ED therapy 56 .…”
Section: Predictors Of Requiring a Penile Prosthesismentioning
confidence: 99%